Nose cavity and paranasal sinus tumors - Michał Konopelko; Olga Padała; Adrianna Krupa; Maciej Putowski; Ewa Piasek (Kazimierz Wielki University, 2019)
Introduction and purpose of paper: The aim of this paper was to present diagnostic and therapeutic difficulties in management of sinonasal tumors, which are extremely rare. First symptoms are not specific, that is why patients usually present with advanced tumors at the moment of diagnosis. Optimal treatment depends upon extent or stage of disease. State of knowledge: Tumors of nose cavity and paranasal sinuses affecting less than 1 in 100 000 people per year. They are result of abnormal proliferation of variety of structures in the nose. Tumors in sinonasal region grow slowly and may invade local structures, for example the skull base, orbit, or brain. Symptoms of tumors of this region are not specific. This is reason why they are often misdiagnosed by the doctors. Proper detection and diagnostic examination require histopathology examination and imaging test such as computed tomography and magnetic resonance imaging. Due to type and stage of tumor, the treatment options are surgery, radiation therapy and chemotherapy, used separate or in combination. Summary: Nasal cavity and paranasal sinus tumors are rare, with a wide spectrum of histological differentiation. The accurate diagnosis of tumor plays a significant role influencing the therapeutic conduct and prognosis.